Risk of frailty and cardiovascular disease in the China Kadoorie Biobank - Kim, D (2023)
Background: Frailty and cardiovascular disease (CVD) are an increasing burden in rapidly ageing societies like China. While frailty and CVD commonly coexist, there is substantial uncertainty about their relationships particularly about the relevance of modifiable CVD risk factors (RFs) for frailty and frailty for CVD. Moreover, frailty research is constrained by a lack of consensus on the optimum definition for frailty with limited evidence on their relative performance. This thesis first compared the measurement properties of the most widely used frailty models, the frailty index (FI) and frailty phenotype (FP), to guide selection of a frailty instrument, and second investigated the associations of CVD RFs with frailty and of frailty with CVD in Chinese adults.